ANALYSIS OF POETRY WRITING ABILITY IN CLASS IV STUDENTS AT ELEMENTARY SCHOOL LEVEL - Erika Apriscilla Verdianti; Tyasmiarni Citrawati (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Writing skill is one aspect of language skills that is very important to be developed from an early age. One of the materials for writing skills at the elementary school level is writing poetry. The purpose of this study was to determine the ability to write poetry in class IV students. This research is a qualitative research type with research subjects namely 31 grade IV students at SDN 232 Gresik, 31 grade IVA students and 30 grade IVB students at SDN 234 Gresik with the main objective to improve poetry writing skills. Data collection techniques were carried out through observation techniques, interviews, questionnaires and tests. The focus of this research is the fourth grade elementary school students. The data analysis technique used is descriptive qualitative analysis technique. Based on the results of this study, it was obtained that 17 students had completed it while 73 students had not completed it. These results indicate that the ability to write poetry in class IV elementary school students still has not achieved the expected results. There are several influencing factors, namely the absence of learning media and the learning model used is still not appropriate